Tahapan Penyusunan dan Analisis Tes Bahasa Arab - Melisa Rezi; Annisa Aulia (Institut Darul Quran Payakumbuh, 2020)
Arabic test is one of the tools for Arabic learning evaluation, where the evaluation is one of the critical components in the Arabic learning curriculum. To get good, meaningful, and meaningful test results, Arab test planning must be consistent with the actual point of composition: (preparation, selection of test materials, determining the number of test items, determining scores, creating lattices, compiling of test items based on lattices, testing of tests compiled), and also requiring an analysis of the conceived and assigned Arabic tests analyzing the level of difficulty, differential and function of the tors, so that the student's Arabic test is valid and religious.